Netter's anatomy coloring book - Hansen, John T. (Philadelphia, PA : Saunders/Elsevier, 2019)
Learn and master anatomy with ease, while having fun,, through the unique approach of Netter's Anatomy Coloring Book. You can trace arteries, veins, and nerves through their courses and bifurcations... reinforce your understanding of muscle origins and insertions from multiple views and dissection layers... and develop a better understanding of the integration of individual organs in the workings of each body system throughout the human form. Whether you are taking an anatomy course or just curious about how the body works, let the art of Netter guide.
Orientation and introduction -- Skeletal system -- Muscular system -- Nervous system -- Cardiovascular system -- Lymphatic system -- Respiratory system -- Gastrointestinal system -- Urinary system -- Reproductive system -- Endocrine system.
Includes index.
Keywords: Anatomy